Validação de sequência didática para (re)construção de conhecimentos estatísticos por professores do Ensino fundamental - Amaral, Fábio Muniz do (2010)
The purpose of this study is to validates a didactic sequence verifying the forms the teachers of elementary Education understand and work the meanings of the center and spread measures, mode, arithmetic and mean average, according to the levels of operation of Aline Robert's knowledge (1998). To reach this objective we elaborated a didactic sequence that contemplates activities in order to contribute in the (re)construction of the meanings of the necessary knowledge so that the teachers have better conditions of applying them in classroom. We discussed the characteristics of the mode, Arithmetic and Medium average, besides the properties that each of those measures presents, using several registrations us to explore all possibilities. Our theoretical references are those proposed by Robert (1998) and the Theory of Semiotic Representation Registers (DUVAL, 2003) to analyze the activities to be used with the teachers. As methodology we used assumptions Didactic Engineering. The analysis of the resolutions and discussions with teachers throughout the implementation process of the sequence revealed their willingness and desire to learn as well as their participation in all the process of (re)construction of knowledge. In this sense we see that the explanation of the meanings of the measures of central tendency for teachers provided greater security for the performance of their work in the classroom, so we infer that the sequence contributed to a better training to the students